Respiratory and Neurological Health Effects of Chromium and PM Exposure among Troso Woven Fabric Workers: A Cross Sectional Study in Jepara - Darundiati, Yusniar Hanani; Joko, Tri; Setiani, Onny; Raharjo, Mursid; Nurjazuli, Nurjazuli; Rahman, Muhammad Auliya (Gema Lingkungan Kesehatan, 2025)
The Troso weaving industry in Jepara, Indonesia, is a traditional craft sector that relies on synthetic dyes and manual production, thereby exposing workers to chromium (Cr) and particulate matter (PM2.5 and PM10) with potential respiratory and neurological risks. This study aimed to analyze their association with respiratory and neurological disorders among workers. A cross-sectional design was applied involving 101 weaving workers from four production sites. Environmental sampling measured Cr concentrations in wastewater and PM2.5/PM10 in the ambient air, while worker characteristics and health complaints were assessed using the ECSC-87 and Q18 questionnaire. Data were analyzed using chi-square tests and odds ratios. Cr concentrations in wastewater ranged from <0.010 to 0.104 mg/L, remaining below the effluent quality standard of 1.0 mg/L but confirming the continuous use of chromium-based dyes discharged without treatment. Average PM2.5 and PM10 levels were 108.75 µg/m³ and 117.75 µg/m³, both exceeding national air quality standards (55 and 75 µg/m³). Bivariate analysis showed that respiratory disorders were significantly associated with exposure duration ≥40 hours/week (OR=7.333; p=0.0001) and working period >5 years (OR=20.935; p=0.0001), whereas dye type, dyeing frequency, and PPE use were not significant. Neurological disorders were significantly associated with exposure duration (p=0.001), working period (p=0.001), type of dye (p=0.0001), frequency of dyeing (p=0.018), and PPE use (p=0.0001). Environmental monitoring confirmed elevated PM levels and chromium-based dye use, while statistical analysis showed that prolonged exposure and long working periods associated with respiratory disorders, and neurological disorders were linked to multiple occupational factors.